2001
DOI: 10.1192/bjp.178.4.344
|View full text |Cite
|
Sign up to set email alerts
|

Handedness, language lateralisation and anatomical asymmetry in schizophrenia

Abstract: Strong evidence is provided for decreased cerebral lateralisation in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
230
1
11

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 409 publications
(262 citation statements)
references
References 87 publications
(94 reference statements)
20
230
1
11
Order By: Relevance
“…Ambidextrousness and mixed-handedness were found to be powerful predictors of reading disability and psychosis, and were over represented in a subgroup of schizophrenic patients with greater cognitive compromise (Cannon et al, 1997;Crow et al, 1996;David et al, 1995;Satz and Green, 1999). Recent studies in schizophrenia support a decreased cerebral asymmetry rather than altered directional asymmetry as the potential candidate phenotype of abnormal lateralization that could contribute to individual susceptibility to schizophrenia (Sommer et al, 2001). In vivo imaging studies also pointed to the loss of asymmetry as a candidate marker to better characterize schizophrenia-associated deficits (Hietala et al, 1999(Hietala et al, , 1995Hsiao et al, 2003;Laakso et al, 2000).…”
Section: Behavioral Lateralization In Dat-ko Micementioning
confidence: 99%
See 3 more Smart Citations
“…Ambidextrousness and mixed-handedness were found to be powerful predictors of reading disability and psychosis, and were over represented in a subgroup of schizophrenic patients with greater cognitive compromise (Cannon et al, 1997;Crow et al, 1996;David et al, 1995;Satz and Green, 1999). Recent studies in schizophrenia support a decreased cerebral asymmetry rather than altered directional asymmetry as the potential candidate phenotype of abnormal lateralization that could contribute to individual susceptibility to schizophrenia (Sommer et al, 2001). In vivo imaging studies also pointed to the loss of asymmetry as a candidate marker to better characterize schizophrenia-associated deficits (Hietala et al, 1999(Hietala et al, , 1995Hsiao et al, 2003;Laakso et al, 2000).…”
Section: Behavioral Lateralization In Dat-ko Micementioning
confidence: 99%
“…A metaanalysis of 19 studies on schizophrenia showed that the prevalence of non-right-handedness was significantly higher in patients than in healthy subjects (Sommer et al, 2001). Similarly, in the meta-analysis of three prospective followup studies, pre-schizophrenic subjects were significantly more often non-right-handed than the general population (Sommer et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PT has been characterized as a computational hub for processing spectrotemporal variation in auditory perception (Griffiths & Warren, 2002), as well as having a role in mapping acoustic speech signals to frontal lobe articulatory networks (Hickok & Poeppel, 2007), and in auditory attention (Hirnstein, Westerhausen, & Hugdahl, 2013). Given these important roles of the PT in speech and language, and its asymmetrical nature in the typically developed brain, there has been much interest in whether individual differences in PT asymmetry are associated with traits that involve changes in language cognition, including dyslexia, reduced verbal ability, and schizophrenia (Eckert et al, 2008;Frank & Pavlakis, 2001;Hasan et al, 2011;Kawasaki et al, 2008;McCarley et al, 2002;Oertel et al, 2010;Shapleske et al, 1999;Sommer, Ramsey, Kahn, Aleman, & Bouma, 2001). These studies have shown that alterations in PT asymmetry may be relevant to some etiological subtypes of these complex traits, although are not necessarily a universal feature of them (Bishop, 2013).…”
Section: Introductionmentioning
confidence: 99%